2018
DOI: 10.1111/1365-2745.12945
|View full text |Cite
|
Sign up to set email alerts
|

Structural and defensive roles of angiosperm leaf venation network reticulation across an Andes–Amazon elevation gradient

Abstract: The network of minor veins of angiosperm leaves may include loops (reticulation). Variation in network architecture has been hypothesized to have hydraulic and also structural and defensive functions. We measured venation network trait space in eight dimensions for 136 biomass‐dominant angiosperm tree species along a 3,300 m elevation gradient in southeastern Peru. We then examined the relative importance of multiple ecological and evolutionary predictors of reticulation. Variation in minor venation network re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 99 publications
1
30
1
Order By: Relevance
“…PCs) directly causes a 1‐SD increase in the response variable (i.e. LMR), after accounting for any other predictor variables (Blonder et al ., ). We followed the same procedure for climate PCs.…”
Section: Methodsmentioning
confidence: 97%
“…PCs) directly causes a 1‐SD increase in the response variable (i.e. LMR), after accounting for any other predictor variables (Blonder et al ., ). We followed the same procedure for climate PCs.…”
Section: Methodsmentioning
confidence: 97%
“…However, previous research in our study region frequently found strong positive relationships between LDMC and leaf herbivory (Schuldt, Assmann, et al, ; Schuldt, Baruffol, et al, ; Schuldt et al, ), possibly because many of the dominant leaf chewers might be adapted to coping with robust leaves in areas where trees with such leaves are common (Pérez‐Harguindeguy et al, ). Such a positive relationship might reflect compensatory feeding to make up for low nutrient contents (see Schuldt et al, ), or correlation with unmeasured traits that affect herbivory, such as secondary plant metabolites (Blonder et al, ). Carbon concentrations and the C:N ratio of leaves are related to palatability, and low C:N ratios in particular have commonly been found to promote herbivory (Pérez‐Harguindeguy et al, ; Poorter et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…A 1 cm 2 sample was cut from the middle of the lamina, excluding any primary veins, chemically cleared, stained, and slide-mounted following standard protocols (Pérez-Harguindeguy et al, 2013;Blonder et al, 2018). Each sample was imaged using a compound microscope (Olympus, BX43) with 2x apochromat objective and an Olympus SC100 color camera (3840 x 2748 pixel resolution).…”
Section: Leaf Vein Imagingmentioning
confidence: 99%
“…Here, we also used HLD to determine scaling relationships, but retained a set of more conventional metrics to compare network architecture across scales. These multi-scale statistics may provide additional insights into how network architecture influences transport, support, defense, embolism resistance, and resilience to herbivory (Sack et al, 2008;Katifori et al, 2010;Brodribb et al, 2016;Blonder et al, 2018).…”
Section: Network Analysis Across Multiple Scalesmentioning
confidence: 99%
See 1 more Smart Citation